Atlas Digital del Plan Regulador del Cantón de Jiménez, Cartago, Costa Rica. - Fernández-Mora, María Alejandra (Instituto Tecnológico de Costa Rica, 2018)
The use of geographic information systems (GIS) has been increasing due to the short time required to perform certain tasks, the low cost and the need for a small number of experts for its implementation. In this way, GIS have become an important tool for a large number of branches of study, such as land use planning. This territorial ordering is carried out in the country through the regulatory plans and the elaboration of a database with layers of different disciplinary axes as part of the requirements of this instrument of planning and management at the local level. The objective of this work was to generate a geographic information base for the creation of the regulatory plan of the cantón of Jiménez, Cartago, Costa Rica. According to the Manual of Regulatory Plans as an Instrument of Territorial Ordering, a total of 106 layers must be prepared for the case of the Cantón de Jiménez; of which 22 were developed in the present graduation project, all with their respective methodologies represented in tutorials and cartographic models, as well as the corresponding metadata. The layer that more work entailed was the use of the soil, which was made with Semi Automatic Classification plugin of the Qgis 3.0 program. The number of elaborated layers was a function of the amount of information to create the layer, the time available and / or the need of knowledge of other professionals in different required subjects.
Trabajo de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018.
Keywords: Sistema de Información Geográfica; Ordenamiento territorial; Capas; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Exogenous earth sciences::Physical geography